Analysis of Madden-Julian Oscillation Phenomenon and its Effect on Rainfall Condition in New Capital City of Indonesia, IKN Nusantara - Nugroho, Anwar Budi; Alhadid, Bai’at; Samoria, Yakubos (Proceeding International Conference on Religion, Science and Education, 2025)
The development of the Indonesian Capital City (IKN) in Indonesia faces major challenges due to hydrometeorological disasters such as floods and landslides. High rainfall fluctuations, coupled with changes in land use, have the potential to increase the risk of hydrometeorological disasters. Therefore, a comprehensive mitigation strategy is needed, including adaptation through climate change and weather studies in determining the direction of infrastructure development, to ensure the resilience and safety of the IKN Nusantara area. MJO is one of the factors that can cause high rainfall fluctuations or extreme rain in the Indonesian region. Therefore, this study examines the influence of the MJO phenomenon on rainfall conditions, especially extreme rain events in the IKN area, with a focus only on MJO phases 3, 4, and 5. This study uses rainfall data for 30 years (1991–2020) from meteorological station observation data and the CHIRPS satellite. The results of the study show that MJO significantly affects rainfall conditions, especially extreme rainfall events in the IKN Nusantara region. In addition, this study also succeeded in identifying areas that have significant responses to MJO phases. Generally, the influence of MJO varies by phase and season, both in terms of monthly rainfall accumulation and extreme rainfall events. Some MJO phases increase the average extreme rainfall by up to 20% when the momentum coincides with humid atmospheric conditions that support the formation of convective clouds in the IKN Nusantara region, while other phases can reduce rainfall by up to 5% due to airflow that inhibits the formation of rain clouds in certain areas. This pattern shows a complex interaction between the MJO and local weather variability, which is influenced by seasonal factors and geographical characteristics of the IKN Nusantara region.